Cytotoxic Activity of Polyphenol Extracts from Three Oregano Species: Hedeoma patens, Lippia graveolens and Lippia palmeri, and Antiproliferative Potential of Lippia graveolens against Two Types of Breast Cancer Cell Lines (MDA-MB-231 and MCF-7) - Marilyn S. Criollo-Mendoza; Rosalío Ramos-Payán; Laura A. Contreras-Angulo; Erick P. Gutiérrez-Grijalva; Josefina León-Félix; Claudia Villicaña; Miguel A. Angulo-Escalante; J. Basilio Heredia (Molecules, 2022)
Oregano infusions have traditionally been used to treat some diseases related to inflammation and cancer; also, some species have shown antiproliferative activity on cancer cell lines, for example, colon and liver, and this has been attributed to its phytochemical profile, mainly its phenolic compounds. This study aimed to evaluate the cytotoxicity and antiproliferative potential of the polyphenols-rich extracts (PRE) of the oregano species H. patens, L. graveolens, and L. palmeri on breast cancer cell lines. The PRE of the three oregano species were obtained from dried leaves. The extract was characterized by determining antioxidant activity, total phenols content, and identifying the profile of phenolic acids and flavonoids by chromatography UPLC-MS/MS. Furthermore, the cytotoxicity of the extracts was evaluated in vitro on a non-cancer cell line of fibroblast NIH3T3 and the antiproliferative potential on the breast cancer cell lines MDA-MB-231 and MCF-7. L. graveolens showed the highest antioxidant capacity and significantly inhibited the proliferation of MCF-7 and MDA-MB-231 cells at non-cytotoxic concentrations in normal cells, with a similar effect to that cisplatin in MDA-MB-231 cells. Therefore, the polyphenol-rich extract from L. graveolens showed the greatest potential to guide future research on the antiproliferative mechanism of action.